L'écologie de la polarisation en tant que stratégie : l’exemple des discours sur l’éducation lors des élections présidentielles de 2021 au Chili - Miguel Stuardo Concha (Amnis)
In this article, based on the grounded theory and discourse analysis methodology, we analyze a series of tweets published during the 2021 Chilean election campaign on the theme of education. Within this framework, we observe nodes of discursive polarization, and analyze the role and strategies of professional political figures in the construction of polarized and polarizing discourses on Twitter. Finally, using an example, we look at how the polarization ecosystem works in an election campaign, and at the influence of traditional media on the production of polarized discourse on social networks.